Post-grazing cutting management in tall fescue affects the sward structure, forage and liveweight production - Scheneiter, Jorge Omar (2019)
Tall fescue is the main perennial grass of the pastures of the temperate region of Argentina. However, after flowering in spring, tall fescue loses productivity and quality. Based on this, the objective of this work was to evaluate the effects of different post‐grazing mechanical cutting managements on the forage mass, leaf proportion, stocking rate, liveweight gain and liveweight production of tall fescue pastures. The treatments were post‐grazing mechanical cutting at anthesis (FC), post‐grazing mechanical cutting throughout spring and summer (SSC), and no post‐grazing mechanical cutting (NC). The experiment was performed from 2011 to 2014 in Argentina. The greatest and lowest forage mass were determined in September–November and May–September respectively. The leaf proportion of the SSC treatment was greater than that of the NC treatment, except in September–November. NC had higher stocking rate and lower liveweight gain than SSC, and neither NC nor SSC differed from FC. The liveweight production of the treatments was characterized by a trade off between stocking rate and liveweight gain. We conclude that FC is an attractive management because, with a single post‐grazing cutting, swards remain productive and leafy.